2010
DOI: 10.1002/jcop.20359
|View full text |Cite
|
Sign up to set email alerts
|

Why rape survivors participate in the criminal justice system

Abstract: After a rape, survivors may seek help from multiple community organizations including the criminal justice system (CJS). Research has found that few survivors report their assaults to the police and of those who do report, many withdraw their participation during the investigation. However, relatively little is known about the factors that lead survivors to participate in the CJS, and how other community services provided by forensic nurses or victim advocates may also help encourage survivor engagement. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 23 publications
7
81
0
1
Order By: Relevance
“…In the current study, participants believed that approaching victims with compassion and respect may offer hope to the victim that they will be treated with respect in subsequent interactions with law enforcement. This finding is consistent with prior research that found victims who experienced respectful treatment by advocates and nurses felt more at ease about participating in the CJ process and anticipated a respectful response by law enforcement (Patterson & Campbell, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, participants believed that approaching victims with compassion and respect may offer hope to the victim that they will be treated with respect in subsequent interactions with law enforcement. This finding is consistent with prior research that found victims who experienced respectful treatment by advocates and nurses felt more at ease about participating in the CJ process and anticipated a respectful response by law enforcement (Patterson & Campbell, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Yet, formal reporting may not be a desired option for all victims. There are potential negative consequences related to reporting, including loss of anonymity, fear of, or experienced, reprisal or pressure to not participate in the criminal justice system by the perpetrator or others, and possible exposure to other potentially harmful negative reactions (e.g., Allen, 2007; Bachman 1998; Felson & Pare, 2005; Patterson & Campbell, 2010; Patterson et al, 2009; Wolitzky-Taylor et al, 2011). Thus, formal reporting cannot be assumed to be an inherent part of the post-rape process, and the focus should be on helping victims to make an informed decision about whether or not to file a report.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Patterson and Campbell's (2010) qualitative data also revealed concerns for justice and social concerns motivating women in their sample to report the rapes to law enforcement. Importantly, the primary motivations of women in their sample to continue their involvement in the investigation process were centered on themes associated with being survivors (e.g., experiencing respect versus revictimization, which increased their confidence).…”
Section: Rape Survivors' Reasons For Help-seekingmentioning
confidence: 90%